The role of Ervl in the mitochondrial import machinery and iron sulphur cluster export machinery in Trypanosoma brucei - Boudová, Michala (Jihočeská univerzita, 2016)
The aim of this thesis was to determine the subcellular localization of Erv1 and to verify its involvement in the cytosolic iron sulphur cluster assembly. Additionally a search for potential interaction partners was conducted, which could possibly assist Erv1 in the processes where it was suggested to take a part, so either in the biogenesis of iron-sulphur cluster proteins or in the mitochondrial protein import, in procyclic T. brucei.
The role of Ervl in the mitochondrial import machinery and iron sulphur cluster export machinery in Trypanosoma brucei